Meta-analisis pengaruh penerapan model inquiry based learning dalam pembelajaran fisika untuk menjawab tantangan kurikulum 2013 pada abad 21 - Esti Aprilia Usman; Mona Trisma Cahyati; Yosa Auliya Putri; Asrizal Asrizal (Universitas Negeri Padang, 2019)
This study aims to determine the effect of the application of inquiry based learning models in physics learning. The effect of applying the IBL model will be investigated from the results of previous studies. This research uses meta-analysis. Meta analysis is the study of a number of research results in the same problem. In this study, the analyzed documents are written about the effect of applying the IBL model in learning Physics. The written documents used were 10 research journal articles taken in accordance with the objectives based on the research theme. The main instrument of this research can help to guide the research documentation itself. Analysis of the data used is qualitative data analysis in the form of narrative from the studies found. The results showed that the application of the IBL model in Physics learning had different effects. The effects of applying the IBL model include understanding Physics concepts, scientific literacy, logical thinking abilities, learning outcomes, creativity, scientific attitudes, critical thinking skills, creative thinking abilities and can reduce misconceptions among students in learning Physics. Therefore, the IBL model can be used as one of the choices of educators to obtain better learning outcomes and the full ability of the students themselves.